The unusual suspects / 2. - Buckley, Michael (Sisters Grimm, 2007)
Although filled with anger over her parents' disappearance, eleven-year-old Sabrina Grimm--along with her grandmother, sister, and several fairy-tale characters--tries to discover who has killed her teacher.